"Brought with the Wind": Magical Realism in Galicia - Volkova, Ekaterina (Madrygal. Revista de Estudios Gallegos, 2018)
The article examines the presence of magical realism in the cultural production of Galicia and explores the reasons for it. For many years, magical realism was considered as a literary phenomenon distinctive of Latin America. However, it is currently believed that magical realism is an international case found in different cultures, including Galicia. Furthermore, magical realism has been detected in cinema and other cultural formats. This research consists in three main sections. First, the theoretical framework explains that magical realism has a particular thematic and structural characteristics. Secondly, a panorama of Galician history and culture reveals that the Galician context is relevant for both aspects of magical realism. Finally, textual and visual analysis detects the features of magical realism in all the studied works: the novel Merlín e familia (1955) by Álvaro Cunqueiro, the novel O lapis do carpinteiro (1998) by Manuel Rivas, the film Sempre Xonxa by Chano Piñeiro (1989) and the graphic novel Ardalén by Miguelanxo Prado (2012). The discussion allows to draw the conclusion that magical realism is a remarkable phenomenon in Galicia.